2023
DOI: 10.1109/access.2022.3151900
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reaction Detection From Social Media Based on Quantum Bi-LSTM With Attention

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Through numerical simulations, experiments indicated that QLSTM learns faster and requires fewer epochs compared to classical LSTM with the same number of network parameters. Building upon Chen et al's research, researchers have made various improvements to QLSTM and applied it extensively in different domains such as speech recognition [11], ocean trajectory prediction [12], sentiment analysis [13], and more. To enhance prediction accuracy, Song et al [14] proposed a mogrifier-quantum weighted memory-enhanced Long Short-Term Memory neural network prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…Through numerical simulations, experiments indicated that QLSTM learns faster and requires fewer epochs compared to classical LSTM with the same number of network parameters. Building upon Chen et al's research, researchers have made various improvements to QLSTM and applied it extensively in different domains such as speech recognition [11], ocean trajectory prediction [12], sentiment analysis [13], and more. To enhance prediction accuracy, Song et al [14] proposed a mogrifier-quantum weighted memory-enhanced Long Short-Term Memory neural network prediction model.…”
Section: Introductionmentioning
confidence: 99%